Self-help materials for smoking relapse prevention: a process evaluation of the SHARPISH randomized controlled trial. (24th February 2017) - Notley, Caitlin; Blyth, Annie; Maskrey, Vivienne; Karavadra, Babu; Brown, Tracey; Holland, Richard; Bachmann, Max O; Brandon, Thomas H; Song, Fujian
Abstract: Background: UK Stop Smoking Services are effective at assisting smokers to quit. However, smoking relapse rates are high, representing a significant public health problem. No effective interventions are currently available. This embedded qualitative process evaluation, within a randomized controlled trial of a self-help smoking relapse prevention intervention, aimed to understand patient perspectives in explaining the null trial finding, and to make recommendations for intervention development. Methods: The intervention was a British version of the 'Forever Free' self-help booklets (SHARPISH—ISRCTN 36980856). The qualitative evaluation purposefully sampled 43 interview participants, triangulated with the views of 10 participants and 12 health professionals in focus groups. Data were thematically analysed. Results: Analysis revealed important variation in individual engagement with the self-help booklets. Variation was interpreted by the meta-themes of 'motivation for cessation', and 'positioning on information provision', interacting with the theme of 'mechanisms for information provision'. Conclusions: Targeting self-help information towards those most motivated to engage may be beneficial, considering the social and cultural realities of individual's lives. Individual preferences for the mechanisms of information delivery should be appraised when designing future interventions. Long-term personalized follow-up may be a simple step in improving smoking relapse rates.